Swallowing in Conversation - Ogden, Richard (Frontiers in Communication, 2021)
Swallowing — a complex physical process that involves closure of the mouth and nasal cavities, as well as the glottis, and the raising and lowering of the larynx — is at the boundary between speech and the body, yet almost nothing is known about how it works in conjunction with speech in spoken interaction. Research into swallowing, mostly in speech therapy, has explored the articulations required, how long it takes the bolus to pass through the mouth to the stomach, and the sounds occur on the way. In the phonetics literature, swallowing is regularly excluded from study: in experiments, tokens with swallowing are excluded; and while swallowing is used to set up certain experiments, its effect on speech is not the object of such studies, though it is sometimes mentioned as a possible action during a stretch of silence, as in word search. Although speaking and swallowing are mutually incompatible, in conversation, swallowing has to be coordinated around the processes of speaking. It can be part of the preparations for speech; it can also occur within and after stretches of speech. While swallowing has been marked in conversation analytic transcripts in several languages, it is almost never commented on. Like sniffing, crying or laughing, swallowing occurs in the vocal tract and may accompany speech, but is not considered as part of the stream of speech. It is clearly related to drinking, which Hoey (2015, 2017, 2020b) shows is strategically placed in the sequential unfolding of talk. In the same spirit, this paper will treat swallowing as an interactional resource which is bound up with language, and which has particular affordances and demands. This paper fills a gap in our knowledge, by focusing on swallowing that is embedded within, before, or after stretches of speech. It considers the phonetic, linguistic and interactional features of swallowing. It thus explores how verbal conduct is intertwined with one aspect of bodily conduct.